Dynamic safety capability: How organizations proactively change core safety systems - Cordery, John; Griffin, M. (2015)
We introduce the concept of “dynamic safety capability” (DSC) to describe an organization’s capacity to proactively change its core safety systems in environments characterized by change and uncertainty. Drawing on theories of dynamic capability in organizations, we define three core features of DSC: (a) sensing via scanning and attending to the future, (b) seizing via integrating complexity and, (c) transforming via enacting second-order change. We propose DSC is developed through organizational learning processes of experience, knowledge articulation, and knowledge codification. The features of DSC are integrated with major theories of safety and approaches to safety management. We discuss how organizational psychology can support the development of DSC through leadership and simulation activities.